Glueballs in peripheral heavy-ion collisions - Natale, A. A. [UNESP] (Elsevier, 1995)
We estimate the cross-section for glueball production in peripheral heavy-ion collisions through two-photon and double-Pomeron exchange, at energies that will be available at RHIC and LHC. Glueballs will be produced at large rates, opening the possibility to study decays with very small branching ratios. In particular, we discuss the possibility of observing the subprocess γγ(PP) → G → γγ.